Monogenic diseases associated with cardiomyopathy genes and their phenotypic manifestations - A. N. Kucher; M. S. Nazarenko (Бюллетень сибирской медицины, 2024)
The aim of the present study was to summarize the data on the spectrum of genetic diseases and their phenotypic manifestations in case of structural and functional defects in 75 genes, pathogenic variants of which are associated with the formation of different types of cardiomyopathy (CMP). The search for scientific publications was carried out in foreign (PubMed) and Russian (eLibrary) digital libraries. The data analysis was performed using the Simple ClinVar, An Online Catalog of Human Genes and Genetic Disorders, and STRING databases.It was shown that the vast majority of CMP genes are pleiotropic. Monogenic diseases caused by mutations in CMP genes are characterized by a wide range of pathological manifestations in various organs and systems (cardiovascular, nervous, endocrine, musculoskeletal systems, connective tissue, skin and appendages, organs of vision and hearing, kidneys) as well as by metabolic and immune disorders. Therefore, if a patient (regardless of the primary diagnosis) has pathogenic / likely pathogenic variants or variants of uncertain significance in the CMP genes, we recommend a detailed and comprehensive clinical examination. This is important for clarifying the effects of rare genetic variants, identifying significant clinical and prognostic features for CMP and monogenic diseases associated with CMP genes, and identifying risk groups and controllable triggers that contribute to the manifestation of pathogenic genetic variants.